SAMBAH – Static Acoustic Monitoring of the Baltic Sea Harbour Porpoise: Harbour porpoise distribution in the Baltic Sea - Carlén, Ida (​SAMBAH – Static Acoustic Monitoring of the Baltic Sea Harbour Porpoise, 2017)
SAMBAH targeted the Baltic Sea population of harbour porpoise (Phocoena phocoena). This population is small and has been drastically reduced during the last decades. The species is listed in Annexes II and IV of the EC Habitats Directive as well as in the national red lists of several Member States. When SAMBAH started, the conservation status of the species in combination with a complex of threats necessitated improved methodologies for collecting data on population size and distribution, and fluctuations over time. The overall objective of the project has been to launch a best practice methodology for this purpose and to provide data for a reliable assessment of distribution and preferred habitats of the species. This would make possible an appropriate designation of SCIs for the species within the Natura 2000 network as well as the implementation of other relevant mitigation measures. The project area encompasses waters between 5-80 metres depth in the Baltic Sea, in the south-east approximately south of latitude 55° 50’ N
(in the Sound) and east of longitude 12° E (in Fehmarn Belt) in the southeast, and south of latitude 60⁰20’N (Åland and the Archipelago Sea) in the north.

SAMBAH objective 1 has been to estimate densities, produce distribution maps and estimate abundances of harbour porpoises in the project area.

SAMBAH objective 2 has been to identify hotspots, habitat preferences, and areas with higher risk of conflicts with anthropogenic activities for the Baltic Sea harbour porpoise.

SAMBAH objective 3 has been to increase the knowledge about the Baltic Sea harbour porpoise among policymakers, managers, stakeholders, users of the marine environment and the general public, in the EU Member States bordering the Baltic Sea.

SAMBAH objective 4 has been to implement best practice methods for cost efficient, large-scale surveillance of harbour porpoises in a low density area.

Purpose:

SAMBAH - Static Acoustic Monitoring of the Baltic Sea Harbour Porpoise - is an international project involving all EU countries around the Baltic Sea, with the ultimate goal to secure the conservation of the Baltic Sea harbour porpoise. Project duration was 2010-2015.

ArcMap raster files showing modelled harbour porpoise distribution (probability of detection) for May-October and November-April. Also included is a shape file for the western management border for the Baltic Proper harbour porpoise population, valid in May-October.
Based on static acoustic monitoring data.

SAMBAH har undersökt Östersjöns population av Vanlig tumlare (Phocoena phocoena). Populationen är liten och har minskat drastiskt under de senaste årtiondena. Arten är upptagen i bilaga II och IV i the EC Habitats Directive samt i de nationella rödlisteförteckningarna i flera medlemsstater. När SAMBAH startade behövde bevarandestatusen för arten, i kombination med en tydligare definierad hotbild, förbättrade metoder för insamling av data om beståndets storlek och fördelning samt fluktuationer över tid. Det övergripande målet med projektet har varit att ta fram en metod för bästa praxis för detta ändamål och att tillhandahålla data för en tillförlitlig bedömning av artens utbredning och föredragna livsmiljöer. Detta skulle möjliggöra en lämplig beteckning av SCI för arten inom Natura 2000-nätverket liksom genomförandet av andra relevanta mildrande åtgärder. Projektområdet omfattar vatten mellan 5-80 meter djup i Östersjön.

Mål 1 för SAMBAH har varit att estimera täthet, producera distributionskartor och uppskatta mängden av tumlare i projektområdet.

Mål 2 för SAMBAH har varit att identifiera hotspots, habitatpreferenser och områden med större risk för konflikter med antropogena aktiviteter i Östersjön.

Mål 3 för SAMBAH har varit att öka kunskapen om Östersjöns tumlare bland bl.a. beslutsfattare, användare av de marina miljöerna och allmänheten i EU:s medlemsstater som gränsar till Östersjön.

Mål 4 för SAMBAH har varit att ta fram förslag på metoder för kostnadseffektiv storskalig övervakning av tumlare i Östersjön.

Syfte:

SAMBAH - Static Acoustic Monitoring of the Baltic Sea Harbour Porpoise - är ett internationellt projekt som involverat alla EU-länder runt Östersjön, med det yttersta målet att säkra beståndet av Östersjöns tumlare. Projektet pågick under perioden 2010-2015.

ArcMap rasterfiler som visar en modellerad utbredning av Vanlig tumlare (sannolikheten för upptäckt) för maj-oktober och november-april.
En shapefil visar den västra gränsen av förvaltningsområdet för beståndet av Vanliga tumlare i Egentliga Östersjön, för maj-oktober.
Baseras på statisk övervakningsdata.
SAMBAH – Statisk akustisk monitorering av tumlare i Östersjön: Utbredning av vanliga tumlare i Östersjön
Keywords: SEA ICE; SALINITY/DENSITY; SALINITY; HALOCLINE; PYCNOCLINE; OCEAN CURRENTS; TURBULENCE; SEA SURFACE TEMPERATURE; WATER TEMPERATURE; THERMOCLINE; POPULATION DYNAMICS; ENDANGERED SPECIES; MARINE; TOOTHED WHALES; distribution maps; distributionskartor; harbour porpoise; vanlig tumlare; red list; rödlistad; habitat preferences; habitatpreferenser; Environment and conservation; Miljö och naturvård; Plants and animals; Växter och djur; Environmental Sciences; Miljövetenskap; Oceans; Kust och hav; Environment; Miljö